Comprehensive biometric, biochemical and histopathological assessment of nutrient deficiencies in gilthead sea bream fed semi-purified diets. Issue 5 (29th July 2015) - Ballester-Lozano, Gabriel F.; Benedito-Palos, Laura; Estensoro, Itziar; Sitjà-Bobadilla, Ariadna; Kaushik, Sadasivam; Pérez-Sánchez, Jaume
Abstract: Seven isoproteic and isolipidic semi-purified diets were formulated to assess specific nutrient deficiencies in sulphur amino acids (SAA), n -3 long-chain PUFA ( n -3 LC-PUFA), phospholipids (PL), P, minerals (Min) and vitamins (Vit). The control diet (CTRL) contained these essential nutrients in adequate amounts. Each diet was allocated to triplicate groups of juvenile gilthead sea bream fed to satiety over an 11-week feeding trial period. Weight gain of n -3 LC-PUFA, P–Vit and PL–Min–SAA groups was 50, 60–75 and 80–85 % of the CTRL group, respectively. Fat retention was decreased by all nutrient deficiencies except by the Min diet. Strong effects on N retention were found in n -3 LC-PUFA and P fish. Combined anaemia and increased blood respiratory burst were observed in n -3 LC-PUFA fish. Hypoproteinaemia was found in SAA, n -3 LC-PUFA, PL and Vit fish. Derangements of lipid metabolism were also a common disorder, but the lipodystrophic phenotype of P fish was different from that of other groups. Changes in plasma levels of electrolytes (Ca, phosphate), metabolites (creatinine, choline) and enzyme activities (alkaline phosphatase) were related to specific nutrient deficiencies in PL, P, Min or Vit fish, whereas changes in circulating levels of growth hormone and insulin-like growth factor I primarily reflected the intensity of the nutritional stressor. Histopathological scoring of the liver and intestine segments showed specific nutrient-mediated changes in lipid cell vacuolisation, inflammation of intestinal submucosa, as well as the distribution and number of intestinal goblet and rodlet cells. These results contribute to define the normal range of variation for selected biometric, biochemical, haematological and histochemical markers.